Louis Harold Gray : A Founding Father of Radiobiology - Wynchank, Sinclair (Springer Biographies, 2017)
This book is a scientific biography of Louis Harold ("Hal") Gray, FRS (1905-65), a pioneer in radiobiology - a little known science that is nevertheless extremely important since it constitutes the basis of radiotherapy. Hal Gray's work also played a vital role in ensuring that radiography would be a safe procedure for the hundreds of millions of persons in whom X-ray pictures have been taken. The book offers fascinating insights into both the history of radiobiology and the life of Hal. It contains much unique biographical material made available to the author over the past 35 years by Hal's contemporaries, many of whom have since died. Great influences on Hal's life and studies, including his unusual high school, Christ's Hospital, and his firm moral beliefs, are described. But his life was not merely a gentle, cloistered existence in academia. Its ups and downs included events that would not have been out of place in a Hollywood drama. The work, the first book-length biography of Hal, is intended for all who enjoy this genre (including those without a scientific background) or have an interest in the history of radiobiology and radiotherapy. .